Does parental employment affect children's educational attainment? Evidence from Germany - Hannah Hörisch (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
This paper analyzes whether there exists a causal relationship between parental employment and children's educational attainment. We address potential endogeneity problems due to (i) selection of parents in the labor market by estimating a model on sibling differences and (ii) reverse causality by focusing on parents' employment when children are aged 0-3. We use data from the German Socioeconomic Panel. Overall, we find little support that parental employment affects children's educational attainment. We can rule out that having a mother who works one hour more per week lowers the probability of high secondary track attendance by more than 0.1%.
urn:nbn:de:bvb:19-epub-2140-9
Keywords: C20; I21; J13; 330; sibling differences; educational attainment; child care; Eltern; Erwerbstätigkeit; Kinder; Bildungsniveau; Weibliche Arbeitskräfte; Schätzung; Deutschland